Analysis of the Role of Health Workers in Efforts to Increase the Coverage of Childbirth Assistance - Siti Halimatul Munawarah; Fikriya Zaharani; Iwan Stia Budi; Ayu Prameswari (Institut Citra Internasional, 2026)
Delivery assistance by health workers plays a crucial role in reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) through the early detection of obstetric emergencies. In the study area, coverage of deliveries assisted by health workers was 71.1% in 2022, increased to 87.36% in 2023, but declined to 82.91% in 2024, remaining below the 100% target. This study aimed to analyze the role of health workers in improving delivery coverage within the working area of Palemraya Health Center. A qualitative approach was employed through in-depth interviews with 11 informants, observations, and document review conducted from May to July 2025. The data were analyzed using thematic analysis through the stages of data reduction, data display, and conclusion drawing with triangulation of sources, methods, and theories to ensure data validity. The study found that the absence of delivery facilities, the persistence of traditional birth attendants, and administrative issues related to maternal domicile were the main barriers to achieving optimal coverage of deliveries assisted by health workers.Recommended efforts include increasing the number of skilled birth attendants, constructing village maternity posts (Polindes),improving facilities, establishing partnerships with traditional birth attendants, and providing education for pregnant women and their families to update their domicile status before delivery.